Building a climate change-resilient food system in Korea: The case of extension and technology dissemination services - Won, Jieun; Babu, Suresh Chandra; Rana, Akriti (International Food Policy Research Institute, 2019)
Climate change affects various stages of the food system including production, processing, distribution, and consumption. To cope with this vulnerability, many nations have engaged in a global movement to establish strategies aimed at food security. As in other countries, in the Republic of Korea climate change has had, and will continue to have, a significant influence on the food system, creating many uncertainties. In response, the Korean government and relevant agencies under national strategies have implemented various policy measures and programs to respond to the effects of climate change and strengthen the country’s food resiliency. In this paper we examine those strategies, measures, and specific programs, and in particular those that involve agricultural extension and technology dissemination. These various sector-specific or cross-sector strategies have not only counteracted climate change impacts but also improved the incomes of farming households, who have struggled with import competition and low profitability under Korea’s generally slowing economy. The Korean government has also implemented extension and tech dissemination projects in and with developing countries with the aim of building resilient food systems in the era of climate change. We find that such programs would benefit from the formation and maintenance of international networks, and moreover, each international program must be preceded by a thorough needs assessment that takes into account the regional context and each project should promote appropriate technologies-that is, technologies customized or particularly suited to the local context.